Molecular Cloning and Functional Analysis of Squalene Synthase 2(SQS2) in Salvia miltiorrhiza Bunge - Rong, Qixian; Jiang, Dan; Chen, Yijun; Shen, Ye; Yuan, Qingjun; Lin, Huixin; Zha, Liangping; Zhang, Yan; Huang, Luqi (Frontiers in Plant Science, 2016)
Salvia miltiorrhiza Bunge，which is also known as a traditional Chinese herbal medicine，is widely studied for its ability to accumulate the diterpene quinone Tanshinones. In addition to producing a variety of diterpene quinone, S. miltiorrhiza Bunge also accumulates sterol, brassinosteroid and triterpenoids. During their biosynthesis, squalene synthase (SQS, EC 2.5.1.21) converts two molecules of the hydrophilic substrate farnesyl diphosphate into a hydrophobic product, squalene. In the present study, cloning and characterization of S. miltiorrhiza Bunge squalene synthase 2 (SmSQS2, Genbank Accession Number: KM408605) cDNA was investigated subsequently followed by its recombinant expression and preliminary enzyme activity. The full-length cDNA of SmSQS2 was 1 597 bp in length, with an open reading frame (ORF) of 1 245 bp encoding 414 amino acids. The deduced amino acid sequence of SmSQS2 shared high similarity with those of SQSs from other plants. To obtain soluble recombinant enzymes, the truncated SmSQS2 in which 28 amino acids were deleted from the carboxy terminus was expressed as GST-Tag fusion protein in Escherichia coli BL21 (DE3) and confirmed by SDS-PAGE and Western Blot analysis, and the resultant bacterial crude extract was incubated with farnesyl diphosphate and NADPH. GC-MS analysis showed that squalene was detected in the in vitro reaction mixture. The gene expression level was analyzed through Quantitative real-time PCR, and was found to be higher in roots as compared to the leaves, and was up-regulated upon YE+ Ag+ treatment. These results could serve as an important to understand the function of the SQS family. In addition, the identification of SmSQS2 is important for further studies of terpenoid and sterol biosynthesis in S. miltiorrhiza Bunge.